Relaxation Psychoeducation in Overcoming Anxiety Talking to Darullughah Wadda'wah Pasuruan Islamic Boarding School Students - Kirana, Dyah Luthfia (Al Musyrif: Jurnal Bimbingan dan Konseling Islam, 2022)
Speaking skills are very important along with the times, so they must be trained early so that speaking skills do not become an obstacle in the future. This study uses qualitative methods with experimental types and comparative descriptive analysis. The process or steps that researchers take in providing relaxation psychoeducation are the first step, Islamic counseling guidance by praying to Allah before doing relaxation exercises. The second step is starting physical relaxation exercises. The third step is dhikr relaxation, the fourth step is psychological relaxation, by remembering and imagining the good intentions and goals you want to achieve. The fifth step of the client. Meanwhile, the results of the implementation of relaxation exercises in overcoming the anxiety of speaking in students of the Darullughah Wadda'wah Islamic Boarding School can be said that this relaxation psychoeducation was quite successful. This can be proven by changes in clients when speaking in public by means of rating scales, and interviews with lodge administrators and lodge friends.